Lipoxins and Annexin-1: Resolution of Inflammation and Regulation of Phagocytosis of Apoptotic Cells. (2006) - Scannell, Michael; Maderna, Paola
Abstract : Phagocytosis of apoptotic cells plays a pivotal role in developmental processes and in the resolution of inflammation. Failed or delayed clearance of apoptotic cells can result in chronic inflammation. Furthermore, clearance of apoptotic cells leads to release of anti-inflammatory cytokines. Recent evidence has shown that endogenous mediators can regulate such processes. In this article, we will review the recognition and signaling mechanisms involved in the phagocytosis of apoptotic cells as well as the role of endogenous compounds that play a relevant role in the modulation of inflammation. The first of these endogenous local mediators to be described are lipoxins (LXs). LXs and aspirin-triggered LXs (ATLs) are considered to act as "braking signals" in inflammation, limiting the entrance of leukocytes to the site of inflammation through inhibition of neutrophil and eosinophil trafficking. LXs are actively involved in resolution of inflammation, stimulating nonphlogistic phagocytosis of apoptotic cells by macrophages. LXA4 and ATLs elicit cellular responses by interacting with a G protein -coupled receptor (ALXR) that is expressed in various cell types. ALXR, originally identified as a low-affinity N-formyl-methionyl-leucyl-phenylalanine receptor-like 1, can bind pleiotropic ligands, i.e., both lipid and peptides, including the glucocorticoid-inducible protein, annexin-1. Interestingly, a role for annexin-1 in phagocytosis has recently emerged. Understanding the role and mechanism of the powerful anti-inflammatory and proresolution actions of endogenous compounds can be a useful tool in the development of potential therapeutics in resolving inflammatory diseases.